PENGEMBANGAN MINAT DAN BAKAT SISWA MELALUI EKSTRAKURIKULER DI MI MA’ARIF MARON - Tri Vina Khasanah; Ahmad Khoiri (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2025)
This study aims to identify and compare the interests and talents of fifth-grade students at MI Ma’arif Maron in various extracurricular activities. The research employed a quantitative approach with a descriptive comparative survey method. The subjects were 35 fifth-grade students. Data were collected using a validated closed-ended questionnaire and analyzed through descriptive statistics to determine the distribution and average levels of students’ interests and talents in each activity. The results revealed that marching band, sports, and BTQ (Qur’an Reading Guidance) and MTQ (Qur’anic Recitation) activities showed relatively high levels of student interest and talent. Marching band activities were favored for promoting discipline and teamwork, although some students found them physically exhausting. Sports activities received very positive responses regarding physical health, team cooperation, and self-confidence, despite the risk of injury. Meanwhile, BTQ and MTQ were highly appreciated for improving Qur’anic reading skills, patience, and recitation abilities, though challenges included reading techniques and performance anxiety. The study concludes that each extracurricular activity offers distinct advantages and challenges. Therefore, schools are encouraged to implement differentiated coaching programs based on the unique characteristics of each activity to optimize students’ interests and talents.